Investigation on the fatigue performance of Ni‐Ti thin wires. Issue 1 (25th February 2016) - Casciati, Sara; Faravelli, Lucia; Vece, Michele
Summary: The fatigue performance of shape memory alloys is one of the main features to assess their potential in most applications (i.e., in vibration mitigation). As experimental results showed, the hysteretic properties of shape memory alloys highly depend on chemical composition, manufacturing process, and loading strain rate. In this paper, commercial wires of Nickel‐Titanium (of diameter 0.2 mm) are investigated. Specimens of different length are tested under cycles of loading‐unloading either on a shaking table or on an MTS Systems Corporation hydraulic testing apparatus (MiniBionix II). The fatigue results of the research campaign are then synthesized in an interpolating model. Copyright © 2016 John Wiley & Sons, Ltd.